From Imitation to Innovation : Public Policy for Industrial Transformation - Agénor, Pierre-Richard; Dinh, Hinh T. (World Bank, Washington, DC, 2014)
What role does public policy play in helping countries accelerate the industrialization process? This note aims to answer this question by applying a framework to analyze the process of transitioning from imitation to innovation. Based on a dynamic model of growth, simulations suggest that learning through imitation may enable firms to improve productivity significantly in a first stage, and that this may eventually benefit innovation activity as well. The model also shows how failure to switch from imitation as the main source of productivity growth to broad-based, homegrown innovation could lead to the 'middle-income trap' that has befallen some countries.